Social representations on forage resources offered by the dry Chaco na- tive forest (Córdoba, Argentina). - SILVETTI, F. (Universidad Nacional del Litoral, 2020)
The paper analyzes the capricultores social representations on forage resources offered by the Dry Chaco native forest (Córdoba, Argentina). The relationship between the historical conditions of access and use of forage by farmers and the symbolic construction of ecosystem is analyzed. It is concluded that farmers express a territorial assessment of the forage that provides the native forest, but particularly that provides the “monte bajo” (scrub), main food source for goats. These representations related to the extensive grazing system is the main strategy of peasant use of forage resources of the territory. This view contrasts with the agrobusiness representatives that support the need to eradicate scrub to seeding new pastures and increase productivity of cattle.